Scheme of virtual machine trusted migration in cloud environment - Jianbiao ZHANG; Yuanxi ZHU; Jun HU; Xiao WANG (网络与信息安全学报)
With the rapid development of cloud computing,as an advantage of cloud services,virtual machine migration technology has been widely noticed and applied.However,there are some problems about VMs migration which should be solved,such as the complication of authentication of platform and the security issues of data transmission,etc.For these problems,firstly,the existing virtual machine migration scheme based on trusted computing technology was analyzed.Secondly,three secure needs that the virtual machine migration scheme which based on trusted computing technology should meet were proposed:the authenticated platform,confidentiality and integrity preserving transfer and atomicity of the vTPCM.Thirdly,a trusted migration scheme of virtual machines for cloud environment was proposed,in which the virtual machine central migration engine and trusted migration agent were introduced to solve the atomicity protection of vTPCM during the migration process.Finally,the concrete scheme was given with verification.